Quantification of constitutive Behavior of sheet metals subjected to dynamic bulge loading - Liu, L; Petrinic, N; Elliot, B; Ruiz, C (2007)
A newly developed method has been employed to quantify the mechanical behavior of sheet metals (both isotropic and orthotropic) subjected to dynamic bulge loading at strain rates of up to 400 s-1. Using newly developed dynamic bulge testing equipment with stereoscopic imaging, the exact shape of the bulging dome has been obtained and represented using high order polynomials before further constitutive analysis. The bulge profile functions discerned have been used to calculate the actual radius of curvature at the pole, thus replacing the spherical shape generally assumed in traditional bulge test analysis. Furthermore, the calculation of the thickness of the bulge has been improved by employing "dome volume" approaches. Effective strain and stress at the dome's pole have been calculated considering both isotropic and orthotropic materials. The effect of gage length on the obtained values of strain and stress has been assessed. Copyright © 2007 by ASTM International.